HUBUNGAN ANTARA WAKTU TUNGGU PELAYANAN RESEP TERHADAP TINGKAT KEPUASAN PASIEN DI PUSKESMAS GAMBUT - Erna Prihandiwati; Normila Hayati; Mochammad Maulidie Alfiannor Saputera; Anna Khumaira Sari (Jurnal Insan Farmasi Indonesia, 2020)
The waiting time for prescription services is one of the services that can affect patient satisfaction. The main aspect that becomes an effect is that the faster the waiting time for prescription services, the patient will be satisfied. In terms of evaluation and service improvement, it is necessary to know the description of the waiting time for prescription services and the relationship between waiting time for prescription services to the level of patient satisfaction. This method of research is non-experimental with prospective data retrieval. The population are patients or families of patients who await in the service of prescription. Samples used consecutive sampling is obtained 169 respondents. Data collection using questionnaires and observation sheets. Data analysis using SPSS 16.0 is the Spearman test. The results showed that the waiting time for the non-blend recipe service and recipes blends as a whole meet the standard SOP Puskesmas Gambut. The level of patient satisfaction on the Reliability dimension with a percentage of 74.06% is in satisfied category. Responsiveness dimensions with a percentage of 76.33% are in very satisfied category. There is no (signification 0.306 > 0.05) relationship between the prescription service waiting time of the patient's satisfaction level in Puskesmas Gambut.